Initial strides for invent-VTE: Towards global collaboration to accelerate clinical research in venous thromboembolism. Issue 163 (March 2018) - Rodger, Marc; Langlois, Nicole; Middeldorp, Saskia; Kahn, Susan; Sandset, Per Morten; Brighton, Timothy; Huisman, Menno V.; Meyer, Guy; Konstantinides, Stavros; Ageno, Walter; Morange, Pierre; Garcia, David; et al.
Abstract: Venous thromboembolism (VTE) represents a major global burden of disease and requires collaborative efforts to conduct large, high-quality investigator-initiated and academically sponsored studies addressing the most relevant clinical questions. Owing to increasing regulatory requirements, the highly competitive nature of peer-reviewed funding and costs associated with conducting large, multinational clinical trials, completing practice-changing research constitutes a growing challenge for clinical investigators. As clinical trialists interested in VTE, we founded INVENT (International Network of Venous Thromboembolism Clinical Research Networks) in an effort to promote and accelerate patient-oriented, investigator-initiated, international collaborative research, to identify, prioritize and answer key clinical research questions for patients with VTE. We report on our activities to formalize the INVENT network and our accomplishments in our first year. Highlights: An international network was proposed to accelerate academically-driven clinical research in venous thromboembolism. The INVENT network was established in 2015 by international research leaders. The strategic direction of INVENT (5 top aspirations) was determined collaboratively.